Benefits and Shortcomings of Laboratory Model Systems in the Development of Genetic Therapies - Bucher, Kirsten; Rodriguez-Bocanegra, Eduardo; Fischer, M. Dominik (Klinische Monatsblätter für Augenheilkunde, 2022)
Gene therapeutic approaches promise treatment or even a cure of diseases that were previously untreatable. Retinal gene therapies tested in clinical trials comprise a wide range of different strategies, including gene supplementation therapies, in vivo gene editing, modulation of splicing mechanisms, or the suppression of gene expression. To guarantee efficient transfer of genetic material into the respective target cells while avoiding major adverse effects, the development of genetic therapies requires appropriate in vitro model systems that allow tests of efficacy and safety of the gene therapeutic approach. In this review, we introduce various in vitro models of different levels of complexity used in the development of genetic therapies and discuss their respective benefits and shortcomings using the example of adeno-associated virus-based retinal gene therapy.
Keywords: gene therapy; retina; in vitro model; AAV